2020
DOI: 10.3389/fncel.2020.592374
|View full text |Cite
|
Sign up to set email alerts
|

Fyn-tau Ablation Modifies PTZ-Induced Seizures and Post-seizure Hallmarks of Early Epileptogenesis

Abstract: Both Fyn and tau have been associated with neuronal hyperexcitability and neurotoxicity in many tauopathies, including Alzheimer's disease (AD). Individual genetic ablation of fyn or tau appears to be protective against aberrant excitatory neuronal activities in AD and epilepsy models. It is, however, still unknown whether ablation of both Fyn and tau can likely elicit more profound anti-seizure and neuroprotective effects. Here, we show the effects of genetic deletion of Fyn and/or tau on seizure severity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 90 publications
(187 reference statements)
3
31
0
Order By: Relevance
“…Our work showed that fyn knockout mice had reduced SE severity following repeated low doses of KA although there was no difference in the amount of KA needed to initiate the first CS (Sharma et al, 2018). In the mouse pentylenetetrazole model, our lab showed that fyn knockout mice had a reduction in SE severity compared to wild type mice though the difference was not significant (Putra et al, 2020b). Importantly, the fyn knockout mice treated with pentylenetetrazole did not have significant neurodegeneration compared to fyn knockout mice without pentylenetetrazole which suggests mitigation of Fyn is neuroprotective.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Our work showed that fyn knockout mice had reduced SE severity following repeated low doses of KA although there was no difference in the amount of KA needed to initiate the first CS (Sharma et al, 2018). In the mouse pentylenetetrazole model, our lab showed that fyn knockout mice had a reduction in SE severity compared to wild type mice though the difference was not significant (Putra et al, 2020b). Importantly, the fyn knockout mice treated with pentylenetetrazole did not have significant neurodegeneration compared to fyn knockout mice without pentylenetetrazole which suggests mitigation of Fyn is neuroprotective.…”
Section: Discussionmentioning
confidence: 71%
“…Following neurological insult, SFKs, more specifically Fyn and Src, are upregulated and can initiate signaling cascades that contribute to neuroinflammation and hyper-excitability (Kaufman et al, 2015;Liu et al, 2016;Nygaard, 2018;Panicker et al, 2019). In neurons, Fyn can modulate both NMDARs, metabotropic glutamatergic receptors, and gamma aminobutyric acid receptors (GABAR) (Salter and Kalia, 2004;Knox and Jiang, 2015;Wang et al, 2016;Jin et al, 2017;Putra et al, 2020b). This regulation can lead to excitotoxicity and to the development of epilepsy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of a non-receptor Src/Fyn tyrosine kinase in neuroinflammation and neuronal hyperexcitability is emerging as a new mechanistic target for the development of drugs for epilepsy and Alzheimer’s disease ( Nygaard et al, 2014 ; Sharma et al, 2018a ; Smith et al, 2017 ). We have recently shown that Fyn, protein kinase C delta (PKCδ), NADPH oxidase 2 (NOX2), and inducible nitric oxide synthase (iNOS) were upregulated during epileptogenesis ( Putra et al, 2019 ; Putra et al, 2020b ; Sharma et al, 2018a ), and in a Parkinson’s disease model ( Gordon et al, 2016 ; Panicker et al, 2015 ). The Fyn-PKCδ-NOX2-iNOS signaling is a novel pathway in epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, NFkB also transcriptionally regulates PKCδ and gp91 phox ( Anrather et al, 2006 ; Gordon et al, 2016 ) implying that it can be a self-perpetuating neuroinflammatory signaling pathway, which could potentially exacerbate seizures ( Gage and Thippeswamy, 2021 ; Vezzani et al, 2011 ). Recently, we demonstrated increased hyperphosphorylated Tau and phosphorylated Src/Fyn and Fyn-tau interaction, using the Proximity Ligation Assay, in neurons at 24 h post-seizure in a mouse model ( Putra et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%